Parasite Industrialism: Antonio Gramsci at ILVA - Collins, Jason (Itinerari, 2023)
Antonio Gramsci’s The Southern Question has been studied as an instrument to understand what happened, not what is happening, within the dynamics of the dialectic regarding industry, government, and Italy’s southern regions. This survey resituates Gramsci’s The Southern Question and his own preceding journal articles that fostered its theories to examine the journalistic mouthpieces of the historic blocs and their opponents, and how these dailies echo the empty narratives used to foster consent to environmental calamity. Under examination are articles reporting on ArcelorMittal’s Taranto Steelworks from The New York Times, Il Corriere della Sera, and Il Manifesto. A contemporary application of Gramsci’s work to these narratives reveals the relevance of his thought in deconstructing hegemonic discourses and their authors’ intentions.